Comparison Full Over Training and Medicine Ball Training Lob Stroke Performance FIK UNM Makassar Students - Bachtiar, Ishak; Syahban, Arham (LITPAM, 2022)
Badminton lob performance requires technical precision, upper-limb power, and the ability to direct the shuttlecock high and deep into the opponent’s backcourt. In university badminton training, lob ability is often practiced technically, yet the comparative effectiveness of specific upper-limb power exercises remains insufficiently documented through experimental evidence. This study examined the effects of full over and medicine ball training on badminton lob stroke performance among students of the Faculty of Sport Science, Universitas Negeri Makassar. A quantitative field-experimental design with a randomized group pretest-posttest structure was used. Forty students who had programmed badminton coursework were selected through simple random sampling and divided into two matched groups: 20 students received full over training and 20 students received medicine ball training. The intervention lasted six weeks with 18 training sessions. Lob performance was measured using a badminton lob test before and after training. Data were analyzed using descriptive statistics, Kolmogorov-Smirnov normality testing, Levene’s homogeneity testing, paired-samples t-tests, and an independent-samples t-test. Full over training increased mean lob performance from 11.10 to 20.75, t (19) = 19.554, p < .001, while medicine ball training increased mean performance from 11.30 to 17.70, t (19) = 14.054, p < .001. The posttest comparison showed a significant difference between groups, t (38) = 2.996, p = .005, favoring full over training. These findings indicate that both training methods improve lob performance, but full over training produces a stronger performance gain in this sample.